Avaliação da microdureza do esmalte dental bovino irradiado com laser ultrapulsado de CO2 e uso de diferentes fluoretos em lesão de cárie incipiente - Oliveira, Márcia Regina Cabral (2016)
Currently, CO2 laser systems are being used to prevent caries by making the enamel acider resistant. As doses for its use are not well established in the literature, the laser use for treatment of incipient lesions has been poorly reported. The aplication of CO2 laser can promote a reorganization of enamel prisms and make the substrate more responsive to fluoride. Fluoride therapy is already well established in the literature; however extensive use protocols require several sessions. Use of laser and fluoride can catalyze remineralization or promote more efficient remineralization. The objective of this study was to evaluate, in vitro, the microhardness values of different forms of fluoride topical application on the artificial caries in bovine dental enamel irradiated with a new parameter of CO2 ultrapulsed laser. The specimens were prepared for a formation artificial caries lesion, and treatment with pH. Our experimental groups applied an ultra-pulsed laser wavelength 10.600nm, pulse interval of 0.99s, pulse rate of 0,005s. (G1) 2% fluoride gel and laser (G2), 1.23% acidulated fluorine phosphate gel and laser (G3) 1.23% fluoride mousse and laser (G4) varnish fluoride and laser (Duraphat 5%) (G5), higid- laser and remineralizing solution (G6), higid- laser and water (G7). The enamel microhardness (KNH) were evaluated with Knoop penetration and 0.098N load, through 5 readings in different areas of the same surface. The analysis were performed after 7, 14, 21, 28 days and its stability after one week of the end of procedures. A two-way (ANOVA) and Tukey were performed. Results described (KNH) after one week of the end of treatment were G1-104.8 (8.3); G2-84.5 (7); G3-99 (4.8); G4-137 (9); G5-214.7 (5); G6-236,16,2; G7-236.1 (9). It can be concluded that the new laser dosimetry methods associated to the use of fluoride or not were able to increase the (MHK) values.